Comparative Chemical Analysis and Bioactive Properties of Aqueous and Glucan-Rich Extracts of Three Widely Appreciated Mushrooms: Agaricus bisporus (J.E.Lange) Imbach, Laetiporus sulphureus (Bull.) Murill and Agrocybe aegerita (V. Brig.) Vizzini - Jovana Petrović; Jasmina Glamočlija; Danijel D. Milinčić; Ana Doroški; Steva Lević; Slađana P. Stanojević; Aleksandar Ž. Kostić; Dušanka A. Popović Minić; Bojana B. Vidović; Ana Plećić; Viktor A. Nedović; Mirjana B. Pešić; et al. (MDPI AG, 2024)
Herein we describe the antioxidant, antimicrobial, antibiofilm, anti-inflammatory and wound-healing potential of aqueous and polysaccharide extracts from three widely appreciated mushrooms: Agrocybe aegerita, Laetiporus sulphureus and Agaricus bisporus. Moreover, we present their detailed phenolic, polysaccharide and protein profiles and ATR-FTIR spectra. The study found that polysaccharide extracts (PEs) from mushrooms had higher total and β-glucan levels than aqueous extracts (AEs), with A. aegerita showing the highest content. L. sulphureus had a higher total protein content, and A. aegerita AE had the highest phenolic content. Our results indicate that all the tested extracts have high potential regarding their bioactive properties, with A. aegerita being the most promising one. Namely, the antibacterial activity assay showed that the development of the skin-infection-causing agent, Staphylococcus aureus, was inhibited with a minimal inhibitory concentration of 4.00 mg/mL and minimal bactericidal concentration of 8.00 mg/mL, while the results regarding wound healing showed that, over the course of 24 h, the A. aegerita extract actively promoted wound closure in the HaCaT keratinocyte cell line model. The anti-inflammatory activity results clearly showed that when we used S. aureus as an inflammation-inducing agent and the A. aegerita aqueous extract in treatment, IL-6 levels reduced to the level of 4.56 pg/mL. The obtained data suggest that the tested mushroom extracts may serve as a source of bioactive compounds, with potential applications in the cosmeceutical, pharmaceutical and food industries. Furthermore, potential skin preparations carefully crafted with mushroom extract may help restore the skin's barrier function, decrease the probability of staph infections and minimize skin irritation.